THE EFFECT OF CALCINATION TEMPERATURE AND HOLDING TIME ON STRUCTURAL PROPERTIES OF CALCIA POWDERS DERIVED FROM EGGSHELL WASTE - Prayitno, Budi; Musyarofah, Musyarofah; Tajalla, Gusti Umindya Nur; Nafisah, Azmia Rizka; Norhidayah, Siti; Kartika, Siska Ayu (Indonesian Physical Review, 2025)
This study investigates the effects of calcination temperature and holding time on the structural properties of calcia (CaO) powders. The raw material used in this study is chicken eggshell waste, which was cleaned, dried, ground, and sieved for uniform particle size. The synthesis of calcia powder was performed by calcining the powder at 900°C and 1000 °C for 5, 10, and 15 hours. XRD, BET, and SEM analyses were employed to evaluate crystal structure, textural properties, and microstructure of the calcined powders. The Rietveld analysis reveals the identified crystalline phases were calcia up to 95.6 mol% and calcium hydroxide as secondary phase. Results indicate that higher calcination temperatures and extended holding times increase particle size and reduce BET surface area, significantly altering pore size distribution. Specifically, elevated temperatures promote sintering and grain growth, leading to smaller average pore radii and decreased total pore volume. The BET surface area ranges from 7.431 m2/g to 1.772 m2/g for samples calcined at 900 °C and from 3.202 m²/g to 0.711 m²/g for samples calcined at 1000 °C. Correspondingly, the average particle radius increases from 183.51 nm to 769.55 nm at 900 °C and from 425.83 nm to 1918.10 nm at 1000 °C as the holding time extends. BJH analysis reveals that longer holding times broaden pore size distribution due to the merging of smaller pores.